Análise comparativa do desempenho entre usinas fotovoltaicas flutuante, em solo e sobre uma edificação, ambas na cidade de Curitiba-PR - Ziwich, Roberson Pereira (2023)
The demand for energy has grown year after year, and there is a need to increase energy and make it available in the national interconnected system, in order to supply all Brazilian consumers, whether residential or commercial, however, to meet the demand in a sustainable way, there are international agreements such as COP21 that guide this increase só that it is carried out with environmental sustainability, aiming to reduce greenhouse gas emissions, seeking the development of sustainable and efficient electricity generation technology. Specifically, distributed generation systems in the photovoltaic modality have seen significant growth according to data from ANEEL, however the floating photovoltaic distributed generation modality has begun its studies in Brazil. The objective of this work is to demonstrate comparisons of the merit index between photovoltaic electrical energy generation systems in floating mode, fixed on the ground and fixed on the roof of buildings, facilitating the evaluation of which installation modes are more efficient. The method used was to prepare a comparison of data through merit indices, enabling the comparison of different photovoltaic plants in a small region in the state of Paraná, including the elaboration of a comparison of expected energy generation calculations in each plant and the obtained It is delivered. This research can be applied in several areas, including the sanitation area, due to the electro-intensive characteristics of these companies, which require a large amount of electrical energy to maintain the entire water supply, collection, treatment and sewage system. These companies normally have dams and flooded areas that enable the application of floating photovoltaic systems, in regions close to large urban centers, a fact that favors investment due to the reduction in necessary infrastructure, however this is not the only factor that favors such a study, others indirect benefits are possible such as reduced evapotranspiration, reduced regulation of algae among other possible benefits such as reduced tariffs. As we concluded, we found that the yield of the plants in general was very close, however small variations are noted in the function of the microclimates in each installation area. This work also presents real performances of plants in operation that present problems throughout the trained period.